Application of the Guha Method in Medical Diagnosis - Cvetkoski, Goran; CHorbev, Ivan (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2010)
The large growth of medical databases has motivated researchers to use data mining on medical data for knowledge discovery. Many mining techniques have been implemented and demonstrated on databases from the medical domain. This paper presents a use of the data mining method GUHA in the discovery process of association rules for the purpose of medical diagnostics. Experiments were performed and the results are presented.